Metafora Bergaya Surealis sebagai Pendekatan Emosi Storytelling Film Animasi Pendek 'Weekends' (2017): metafora surealis, emosi, animasi - Sharon Leman; Dianing Ratri; Irfansyah Irfansyah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
The animated short film “Weekends” (2017) by Pixar story artist, Trevor Jimenez, tells the story of his childhood life, which he shuttled from place to place due to the circumstances of his divorced parents. This film depicts sadness and confusion that often occurs to a child from a broken-home family. By using surrealism-style metaphors, the film explores the subconscious and dream images as one of the character's emotional depictions.Surrealism is a visual style that depicts conditions that may not occur in the real world. It is used in the film as a middle ground to analogize abstract objects (such as emotions) into real objects. This research focused on analyzing how surrealism metaphors describe the various types of emotions that exist in the film.